Measurement and Analysis of learning Engagement of South-Asian Students in Chinese Universities 南亚国家来华留学生个体学习性投入的测量与分析 - Yu, Lan; Zhu, Shucheng (Journal of International Students, 2020)
International students’ learning experiences and learning outcomes in intercultural contexts are important topics in higher education internationalization. This study focused on South-Asian students studying at Chinese universities. To assess the participants’ academic engagement during their study at Chinese universities, the Individual South-Asian Student Engagement Questionnaire was developed. Through the use of exploratory factor analysis and correlation analysis on a sample of 193 South-Asian students in China, the research confirmed the reliability and validity of the instrument. Four dimensions, i.e. learning motivation, learning behaviors, learning strategies and learning outcomes, as well as the interactions between the four dimensions, were suggested to understand the features of South-Asian students’ learning engagement during their studies in Chinese higher education institutions. 国际学生在跨文化情境下的学习体验与收获是高等教育国际化研究领域的重要议题。本研究选取具有区域性、国别化特征的南亚国家来华留学生为研究对象，通过实施来华留学生个体学习性投入调查收集数据，采用统计学分析检验该测量工具的信效度，同时呈现南亚留学生在学习动机、学习行为、学习策略和学业成就四个维度的关键性表征及其互动关系。